2014
DOI: 10.1007/s40242-014-4054-6
|View full text |Cite
|
Sign up to set email alerts
|

New half-sandwich zirconium(IV) complexes containing salicylaldimine ligands: Synthesis, characterizations and catalytic properties

Abstract: Two new half-sandwich zirconium(IV) complexes bearing salicylaldimine ligands of the type Cp*Zr[2-t Bu-4-R-6-(CH=N i Pr)C 6 H 2 O]Cl 2 [R=H(1), t Bu(2)] were prepared by the reaction of Cp*ZrCl 3 with the corresponding lithium of salicylaldimine ligands 2-t Bu-4-R-6-(CH=N i Pr)C 6 H 2 OLi[R=H(LiLa), t Bu(LiLb)]. Complexes 1 and 2 were characterized by 1 H NMR, 13 C NMR spectroscopy and elemental analysis. When activated with Al i Bu 3 and Ph 3 CB(C 6 F 5 ) 4 , both complexes 1 and 2 exhibited reasonable cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Fig.4 By analyzing the structure of the transition metal catalyst and the metallocene catalyst of salicylaldehyde imide, it is found that the zeolite of the bis-salicylaldehyde imide Ti has a octahedral structure, similar to the tetrahedral structure of the zirconocene and zirconocene catalyst and the catalyst with these structures has good polymerization properties. Huang et al [21] synthesized a series of monocarbamate Schiff base mixed ligand Zr complex (catalyst 29 ~ 31). The eff ects of substituents on cyclopentadiene on the copolymerization of ethylene / 1-hexene were investigated.…”
Section: Catalytic Olefi N Copolymerization To Prepare Functional Polmentioning
confidence: 99%
“…Fig.4 By analyzing the structure of the transition metal catalyst and the metallocene catalyst of salicylaldehyde imide, it is found that the zeolite of the bis-salicylaldehyde imide Ti has a octahedral structure, similar to the tetrahedral structure of the zirconocene and zirconocene catalyst and the catalyst with these structures has good polymerization properties. Huang et al [21] synthesized a series of monocarbamate Schiff base mixed ligand Zr complex (catalyst 29 ~ 31). The eff ects of substituents on cyclopentadiene on the copolymerization of ethylene / 1-hexene were investigated.…”
Section: Catalytic Olefi N Copolymerization To Prepare Functional Polmentioning
confidence: 99%
“…The steric hindrance of catalyst 31 was the largest, but the catalyst activity was the highest, achieving 1.2 × 106 g of copolymer/(mol Zrh. In 2014, Liu et al [22] synthesized two novel monocarbophore Schi-base mixed ligand Zr complexes 32 and 33, and the phenoxy groups were Bu substituents to catalyze the ethylene/1-hexene copolymerization. The relative molecular mass of the activity and the polymerization product is higher than that of the unsubstituted catalyst, which is due to the electron effect of the t Bu substituent, which stabilizes the cationic active center of the catalyst and increases the catalytic activity.…”
Section: Catalytic Olefin Copolymerization To Prepare Functional Poly...mentioning
confidence: 99%